2018
DOI: 10.1159/000492298
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Human Adipose-Derived Stem Cell Exosomes in Stress Urinary Incontinence – An in Vitro and in Vivo Study

Abstract: Background/Aims: To evaluate whether local injection of exosomes derived from human adipose-derived stem cells (hADSCs) facilitates recovery of stress urinary incontinence (SUI) in a rat model. Methods: For the in vitro study, a Cell Counting Kit-8 (CCK-8) array and proteomic analysis were performed. For the in vivo study, female rats were divided into four groups: sham, SUI, adipose-derived stem cell (ADSC), and exosomes (n = 12 each). The SUI model was generated by pudendal nerve transection and vaginal dila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…Accumulating evidence indicates that exosomes derived from ADSCs have the ability to treat various diseases, including diabetes ( Zhao et al, 2018 ), stress urinary incontinence ( Ni et al, 2018 ), amyotrophic lateral sclerosis ( Lee et al, 2016 ), and ischemia/reperfusion injuries ( Pu et al, 2017 ). To examine their effect on a model of ischemic injury, we isolated primary ADSCs from C57/Bl6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence indicates that exosomes derived from ADSCs have the ability to treat various diseases, including diabetes ( Zhao et al, 2018 ), stress urinary incontinence ( Ni et al, 2018 ), amyotrophic lateral sclerosis ( Lee et al, 2016 ), and ischemia/reperfusion injuries ( Pu et al, 2017 ). To examine their effect on a model of ischemic injury, we isolated primary ADSCs from C57/Bl6 mice.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that exosomes derived from stromal fibroblasts could enhance the drug resistance to colorectal cancer [37]. Furthermore, adipose-derived stem cells could secrete exosomes, which in turn exhibit biological effects on tissue regeneration and could protect against tissues of bone, muscle, skin, and brain [38].…”
Section: Discussionmentioning
confidence: 99%
“…This new MSCs-based therapy, known as acellular therapy, can provide therapeutic benefits without the need to transplant living cells, making the process easier to be standardized and reducing cell transplant related risks. Several attempts have been made to investigate the therapeutic effects of MSC secretome in PFDs (Table 3), by utilizing the concentrated conditioned media (CCM) of MSCs [64,88] or the exosomes derived from MSCs [89] [90].…”
Section: Mscs-derived Secretome For Pfdsmentioning
confidence: 99%